2020
DOI: 10.1002/alr.22691
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin in high‐risk, refractory chronic rhinosinusitus after endoscopic sinus surgery and corticosteroid irrigations: a double‐blind, randomized, placebo‐controlled trial

Abstract: Background Refractory chronic rhinosinusitis CRS remains a significant burden for patients o en leaving them with few therapeutic options that provide low-morbidity long-term and meaningful symptomatologic and endoscopic disease improvement Macrolides have long been thought to offer both an immunomodulatory and antimicrobial effect Our objective was to evaluate the efficacy of low-dose long-term azithromycin in a carefully selected high-risk population failing appropriate medical therapy of budesonide nasal ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
(55 reference statements)
1
13
0
Order By: Relevance
“…At the 4‐month time point, 59 patients (50%) attained optimal outcomes, while 59 patients (50%) showed persistence of disease and was deemed nonresponsive to ESS. Patients included needed at least 1 of the following criteria used to qualify them at high risk of disease recurrence: history of previous sinus surgery; sinus surgery at ≤38 years of age; absolute eosinophilia ≥500 cells/mm; total serum immunoglobulin E levels ≥150 kIU/L; sinus culture of a Gram‐negative organism at any time‐point; and intraoperative finding of eosinophilic mucin 11 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the 4‐month time point, 59 patients (50%) attained optimal outcomes, while 59 patients (50%) showed persistence of disease and was deemed nonresponsive to ESS. Patients included needed at least 1 of the following criteria used to qualify them at high risk of disease recurrence: history of previous sinus surgery; sinus surgery at ≤38 years of age; absolute eosinophilia ≥500 cells/mm; total serum immunoglobulin E levels ≥150 kIU/L; sinus culture of a Gram‐negative organism at any time‐point; and intraoperative finding of eosinophilic mucin 11 …”
Section: Methodsmentioning
confidence: 99%
“…Patients included needed at least 1 of the following criteria used to qualify them at high risk of disease recurrence: history of previous sinus surgery; sinus surgery at ≤38 years of age; absolute eosinophilia ≥500 cells/mm; total serum immunoglobulin E levels ≥150 kIU/L; sinus culture of a Gram-negative organism at any time-point; and intraoperative finding of eosinophilic mucin. 11 Tissue samples were obtained by a mucosal brushing at the surface of the middle meatus at the time of surgery and at the 4-month time point. Total RNA was extracted from brushings using the RNeasy Mini Kit (Qiagen) according to the manufacturer's instructions and stored at −80°C until microarray measurements.…”
Section: Clinical Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…Renteria et al 6 demonstrated that Staphylococcus aureus abundance in the sinonasal microbiome of patients with chronic rhinosinusitis (CRS) was decreased after 4 months of thrice weekly, low-dose azithromycin versus placebo in a double blind, randomized trial. Maniakas et al 7 conducted a double-blind, randomized trial demonstrating that low-dose oral azithromycin aids polyp resolution in patients with persistent polyposis despite ESS and high-volume corticosteroid irrigations. Siu et al 8 performed a randomized study of 30 patients undergoing ESS and analyzed sinonasal and stool samples using RNA sequencing.…”
Section: Chronic Rhinosinusitismentioning
confidence: 99%
“…Several studies have shown that the presence of bacterial biofilms has a negative impact on the healing process after ESS leading to persistence of postoperative symptoms and mucosal inflammation ( Bendouah et al., 2006 ; Psaltis et al., 2008 ; Singhal et al., 2011 ). A recent study looking at the contribution of microbes in early disease recurrence after ESS found that perioperative positive culture with S. aureus was associated with poor outcomes, and that clearance of the bacteria led to 75% remission at 4-months after surgery ( Maniakas et al., 2020 ). Focusing therapy on clearing perioperative infections in the initial postoperative period may alter the deleterious impact that bacterial pathogens have on the regeneration of epithelium and repopulation of the microbiome.…”
Section: Introductionmentioning
confidence: 99%